PERANAN PERSONAL SELLING DALAM USAHA MENINGKATKAN VOLUME PENJUALAN JASA PERIKLANAN PADA PT GRANTON WORLD PALEMBANG (Studi kasus pada perusahaan Periklanan) - HL. Suhairi Hazisma; Yusnizal Firdaus (Jurnal Media Wahana Ekonomika, 2014)
This research is to look at the role of personal selling activities in increasing the volume of sales of advertising services at PT Granton World Palembang. It is located at Jalan Demang Lebar Daun No 59A Palembang. The authors found a decrease in sales volume that is from 2012-2013. Data was collected by using interviews and literature study.  Personal selling as a direct communication with prospective customers or individual customers on how to deliver information products or services to be offered. The results of research that the decrease in sales volume due to the amount of labor decrease too. That is because the salesperson has only minimal knowledge of how good sales, the functions and duties as a sales force to market the company's products as well as the lack of continuous training.  Therefore, PT Granton World Palembang should increase the potential, skills and motivation of sales person and equip sales person with product knowledge to more understand about the various advantages of the product to increase sales volume. Keywords : personal selling, advertising, services, product